Influence of Plant Growth Regulators on shoot and root length of Fagopyrum esculentum Moench of Himalayan Region - Jamwal, Komal; Bhattacharya, Sujata; Puri, Sunil; Sharma, Dushyant (International Journal of Economic Plants, 2020)
Present investigation was made to evaluate effect of PGRs on shoot and root length of Fagopyrum esculentum. Results revealed that there was increase in shoot length by GA at 100 mg l-1 and root length by IAA at 50 mg l-1 at 30, 60 and 90 days of plant growth. ABA at 25 mg l-1 and 100 mg l-1 decreased shoot length as well root length. BAP at 100 mg l-1 also decreased root length. In combinations, IAA+GA 100 mg l-1 treatment enhanced shoot length as well as root length. Decrease in shoot length was observed in IAA+ABA, ABA+BAP (50 and 100 mg l-1) and root length by ABA+BAP (100 mg l-1) treatment.